Effect of Oxidative Roasting on Selective Leaching of Lithium from Industrially Shredded Lithium Iron Phosphate Blackmass - Ayesha Tasawar; Daniel Dotto Munchen; Alexander Birich; Rungsima Yeetsorn; Bernd Friedrich (Metals, 2025)
The increasing need-based demand for lithium iron phosphate (LFP) batteries in electric vehicles and energy storage systems necessitates the development of efficient and sustainable recycling methods. This study investigates the effect of oxidative roasting on lithium extraction from industrially sourced LiFePO4 (LFP) blackmass containing high graphite content (~46%) and mixed electrode materials. Roasting at 650 °C for one hour converted LiFePO4 into water-soluble Li3Fe2(PO4)3 and Fe2O3, while reducing carbon and fluorine levels. However, contrary to expectations, mild-acid leaching (pH 2, 40 g/L, 20 °C) of roasted blackmass did not improve lithium recovery compared to unroasted material, yielding approximately 33% extraction efficiency. Strong-acid leaching (pH 0, H2SO4/H2O2) achieved over 95% lithium recovery but also resulted in significant co-dissolution of iron and other impurities. Our XRD and SEM analyses showed that some lithium-containing phases remained in the residue after water leaching, while acid leaching left mainly iron oxide and graphite. These results suggest that, for complex and graphite-rich industrial blackmass, roasting may not always deliver the expected boost in lithium recovery. Our findings highlight the need to tailor recycling processes to the specific characteristics of battery waste and suggest that direct hydrometallurgical methods could be more effective for complex, impurity-rich LFP blackmass streams.